The Influence of Dust Density and Its Grain Size On the Polycrystalline PV Panel Electric Power Production - Al-Sawalmeh, Wael H.; Abu Shehab, Wael; Al-Shabaan, Ghadeer; Alrashdan, Mohd H. S. (جامعة الحسين بن طلال - عمادة البحث العلمي والدراسات العليا, 2019)
polycrystalline PV is one of the most solar cell types available in the market for domestic use due to its cost and its favorable efficiency. The output electrical power generated using polycrystalline PV cells depends on many parameters including the dust covered its surfaces during use. This research investigates the influence of dust grain size and its density on the output power produced using Polycrystalline PV panel. Three different of dust grain size and densities are tested in Al-Hussein Bin Talal University mining laboratory under steady conditions, then used to covered polycrystalline PV panel with different densities. maximum output power is measured at simple resistive load once the panel not covered with dust, this experiment repeated three time and the output power reduction is measured three times when the panel is covered with three types of dust with different grain size. There is inversely relationship with dust grain size covered the panel and the maximum output generated, furthermore, there is proportional relationship between the dust density and the output power generation, this results will open the door in front of solar farms using polycrystalline PV panels in different areas in taking an actions in cleaning process at specific times depend on environmental conditions at that area.
Keywords: الخلايا الكهروضوئية -- الهندسة الكهربائية -- الألواح الشمسية الكهروضوئية -- الطاقة الشمسية الكهروضوئية